Integrasi Kurikulum Nasional dan Budaya Lokal: Transformasi Manajerial dalam Meningkatkan Mutu Pendidikan di Kota Sorong - Anwar, Zakiyah; Rusdi; Fitri Cahaya (Kilau Publishing, 2025)
This study was motivated by the importance of adaptive managerial strategies in responding to the dynamics of primary education. Schools are required not only to excel academically but also to maintain cultural relevance. SD Negeri 21 Kota Sorong was chosen as the subject because of its uniqueness in managing the diversity of students' backgrounds amid limited facilities. The purpose of this study was to examine the principal's strategic steps in creating a holistic learning environment through the optimisation of available resources. The method used was a qualitative approach with structured interviews with the principal as a key informant to obtain comprehensive managerial data. The results of the study show that the school has succeeded in integrating the national curriculum with a local wisdom based curriculum. Active collaboration with parents through the school committee and improving teachers' technological competencies are the main pillars in supporting successful learning in the digital era. The conclusion emphasises that the synergy between humanistic human resource management and technological adaptation is the key to creating an inclusive and responsive educational ecosystem that is tailored to the characteristics of the region